Dampak Climate Change Dan Ketahanan Pangan Selama Kehamilan Pada Ibu Hamil Di Pedesaan Indonesia: Studi Kualitatif Dampak Badai El Nino - Ernawati, Ernawati; Wijaya, Yosi Maria; Elsanti, Devita; Sumarmi, Sumarmi; Rahayu, Mesra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Agriculture and food are negatively impacted by climate change, especially the long dry season caused by El Niño in Indonesia, especially in rural areas. High dependence on rainfall, land, and lack of representation in decision-making groups result in increased challenges and limited adaptive capacity of pregnant women in climate change including its impact on food security. Objectives: This study aims to characterize: 1) sensitivity to decreased food security related to El Niño for pregnant women; 2) pregnant women's perceptions of the impact of El Niño on food security during pregnancy; and 3) changes in food security and maternal and infant health over time, as observed by pregnant women in rural Indonesia. Methods: This study design is a qualitative design. This study was conducted in one district in South Sulawesi and Central Java Provinces. A semi-structured interview guide was used. Data analysis using qualitative thematic analysis methods of data using the constant comparative method. Transcripts were uploaded to NVivo© 12 to facilitate manual coding. with the constant comparative method and thematic analysis. Results: All informants did not know or did not understand the term El Niño. The most felt impacts due to the long dry season are drought and strong winds that make it difficult to obtain food. The way to overcome food insecurity is to utilize food that is still available to be processed into food that can be consumed and shared or shared with family to survive. Conclusion: Climate change has a significant impact on food security, especially in rural areas, which results in the risk of malnutrition in pregnant women.